2007
DOI: 10.1177/1545109706298405
|View full text |Cite
|
Sign up to set email alerts
|

HIV Infection Among Transport Workers Operating Through Siliguri-Guwahati National Highway, India

Abstract: A community-based cross-sectional study was conducted in July 2004 to understand the problem of HIV and other sexually transmitted infections among long-distance transport workers operating through the Siliguri-Guwahati national highway. The study included 301 transport workers who were contacted at different transport workers' stops on the Siliguri-Guwahati national highway. Informed consent was obtained. Participants were interviewed for their socio-demographic characteristics, risk behavior, and risk percep… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
14
0

Year Published

2008
2008
2023
2023

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(16 citation statements)
references
References 10 publications
1
14
0
Order By: Relevance
“…Substantial proportions of truckers also have sexual relations with non-paid female partners [14–16] and only about one-third use condoms consistently in such sexual encounters [15, 16]. Studies in the country have found high HIV prevalence (2–16 %) [14, 15, 17, 18] and high STI prevalence (3–13 %) among truckers [15, 17, 18]. …”
Section: Introductionmentioning
confidence: 99%
“…Substantial proportions of truckers also have sexual relations with non-paid female partners [14–16] and only about one-third use condoms consistently in such sexual encounters [15, 16]. Studies in the country have found high HIV prevalence (2–16 %) [14, 15, 17, 18] and high STI prevalence (3–13 %) among truckers [15, 17, 18]. …”
Section: Introductionmentioning
confidence: 99%
“…6 Studies in the country have found high HIV (2-13 %) and high STI prevalence (3-16 %) among long distance truck drivers. 4,11,12 Therefore the present study aimed to examine the risk behaviors and Prevalence of STI's among Long distance truck drivers in association with their age, education, length of time away from home and CSW's exposure.…”
Section: In 21mentioning
confidence: 99%
“…We also noticed that most of the studies included only the drivers and ignored their helpers despite the fact that the later have been found to have higher vulnerabilities towards HIV [23] [38] [39] [77]. Many studies which included both drivers and helpers provided aggregate level figures and they did not present the findings separately for drivers and helpers [19] [29] [32] [36] [43]. Only few such studies presented selected indicators separately for both drivers and helpers [23] [31].…”
Section: Discussionmentioning
confidence: 99%
“…Few studies in which truckers were recruited from clinics established to treat STIs found much higher prevalence of HIV ranging from 16% -57% [19] [29] [44] [45]. Studies during early 2000 found high prevalence of syphilis (6.3%) and Hepatitis B (4% to 6%) among truckers [32] [43]. Recent studies conducted towards the end of 2000 found relatively lower prevalence of syphilis ranging from 1.7% -2.7% [16] [17].…”
Section: Sexual Behaviors and Prevalence Of Sti/hiv Among Truckers Inmentioning
confidence: 99%